COMMUNITY SERVICE APPLICATIONS FOR VILLAGE OFFICE USING LARAVEL FRAMEWORK - Damyati, Fitri; Nuryani, Ely; Hasanah, Huswatun; Ruhiawati, Irma Yunita; Oktavani, Nicko (Jurnal Sistem Informasi dan Informatika (Simika), 2024)
The government has developed a population administration system to support public services, one of the media used by the government is electronic government (e-government). One of the villages that has a large Regional Revenue and Expenditure Budget (APBD) in the Serang district, Banten province is Ranjeng village, Ciruas sub-district. The problem is that data management in villages is still carried out semi-manually, there is no specific application to handle this management so it is not time efficient, reporting and the level of service to the community is less than optimal. To overcome these problems, a system is needed that can help the community in submitting letters and can help the village government to improve services to the community. The system design used in this research is using the Waterfall method so that it is easier to develop and using UML (Unified Modelling Language) for visual system modelling, while the programming language used is PHP using the Laravel framework. The final result of this research is a system that can improve the services of the Ranjeng Village Office to the community to be optimal.